COPS-SLS a service level negotiation protocol for the Internet. - Thi Mai Trang Nguyen
The deployment of QoS over the Internet may achieve protocols for the negotiation of service levels, as well as mechanisms for the end-to-end realization of service level agreements. Such general-purpose protocols include Common Open Policy Service (COPS) for policy specification within a domain. This article proposes an extension of the COPS protocol for intra- and interdomain service level negotiation. The proposed protocol is known as COPS-SLS. This allows the configuration of domain policies regarding service levels, and the automatic negotiation of service levels within the domain policies
Keywords: COPS protocol; COPS-SLS.; Common Open Policy Service; IP networks; Internet; QoS; Automatic negotiation; Domain policies negotiation; General-purpose protocols; Inter-domain service level negotiation; Intra-domain service level negotiation; Policy specification; Policy-based networking; Service level agreements; Service level negotiation protocol